2018
DOI: 10.1111/jace.16019
|View full text |Cite
|
Sign up to set email alerts
|

Differences in surface failure modes of soda lime silica glass under normal indentation versus tangential shear: A comparative study on Na+/K+‐ion exchange effects

Abstract: The effects of exchanging Na+ with K+ on the mechanical and mechanochemical properties of a soda lime silica (SLS) glass were investigated. It is known that replacing smaller modifier ions with bigger ions in the silicate glass network, at temperatures below the glass transition (Tg), produces a compressive stress in the subsurface region that enhances resistance to mechanical damages. This study found that when Na+ ions in SLS are exchanged with K+ ions at 400°C, the hardness, indentation fracture toughness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 66 publications
(95 reference statements)
6
27
0
Order By: Relevance
“…Previous studies have shown that the ν Si‐O, as red‐shift after chemical tempering (K + ion‐exchanged SLS) is due to an increase in the Si‐O bond length, but that the wear resistance deceases for such glasses . This supports the hypothesis that strained bonds may influence the mechanochemical reactions occurring at high humidity and decrease the wear resistance of the glass.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Previous studies have shown that the ν Si‐O, as red‐shift after chemical tempering (K + ion‐exchanged SLS) is due to an increase in the Si‐O bond length, but that the wear resistance deceases for such glasses . This supports the hypothesis that strained bonds may influence the mechanochemical reactions occurring at high humidity and decrease the wear resistance of the glass.…”
Section: Discussionsupporting
confidence: 72%
“…The HS process is not as controlled as the TT process and often results in asymmetric residual stress patterns . Previous works using a ball‐on‐flat tribometer showed peculiar wear behaviors of the SLS glass as a function of relative humidity (RH) of the testing environment . In dry conditions (0% RH), the materials harder than SLS mechanically abrade and scratch the glass surface which is in accordance with the Reye‐Archard‐Khrushchov wear criterion .…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…11 Such understanding is often generated by examining the initiation of well-defined defects, for example, generated using sharp Vickers or Berkovich indenter tips 3 or wedges. 12,13 Also on chemically strengthened glasses, indentation deformation and cracking, 8,[14][15][16][17][18][19][20][21] scratch resistance, [21][22][23][24] abrasive wear, 20 and the response to impact load 16,17,25,26 were extensively studied over the past years. However, sharp contact experiments such as underlying most of these studies represent rather harsh conditions, with local stress easily approaching the range of 10 GPa.…”
mentioning
confidence: 99%